Molecular Mechanisms of Actions of Formulations of the Thyroid Hormone Analogue, Tetrac, on the Inflammatory Response. (May 2013) - Davis, Paul J.; Glinsky, Gennadi V.; Lin, Hung-Yun; Incerpi, Sandra; Davis, Faith B.; Mousa, Shaker A.; Tang, Heng Yuan; Hercbergs, Aleck; Luidens, Mary K.
<x xml:space="preserve">Abstract</x> Background. Tetraiodothyroacetic acid (tetrac) and its nanoparticulate formulation (Nanotetrac) act at a cell surface receptor to block angiogenesis and tumor cell proliferation. Objective. The complex anti-angiogenic properties of tetrac and Nanotetrac caused us to search in the literature and in certain of our unpublished mRNA experiments for evidence that these agents affect the early inflammatory response, perhaps through actions on specific cytokines and chemokines. Results and Discussion. Tetrac and Nanotetrac inhibit expression in tumor cells of cytokine genes, e.g., specific interleukins, and chemokine genes, such as fractalkine (CX3CL1), and chemokine receptor genes (CX3CR1) that have been identified as high priority targets in the development of inflammation-suppressant drugs. The possibility is also examined that tetrac formulations have an effect on the function of inflammatory cells.